Changes in fed cattle marketing methods: survey results - Ward, C.; Lawrence, J.; Feuz, D.; Schroeder, Ted C. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Significant changes in fed cattle marketing methods have occurred over time. This report summarizes a survey conducted to determine current and intended marketing practices of cattle feeders. Use of marketing agreements has increased over time. In 1996, 23% of cattle fed by survey respondents were sold under some type of marketing agreement. This increased to 52% in 2001 and was expected to increase to 65% by 2006. Use by cattle feeders of cash live and carcass weight pricing is expected to decline, and grid pricing is expected to increase substantially over time. The percentage of cattle that survey respondents marketed using cash markets declined from 82% in 1996 to 53% in 2001, and it is expected to be only 33% by 2006. Grid pricing increased from 16% of marketings in 1996 to 45% in 2001, and this is expected to reach 62% by 2006. Respondents indicated a strong desire to have grid base prices tied to boxed beef or retail markets, but a slightly less strong desire to have base prices negotiated.
Keywords: Beef; Marketing methods; Cattle feeders